A rare case of Weissella confusa endocarditis. (November 2021) - Hurt, William; Savarimuthu, Sugeevan; Mughal, Nabeela; Moore, Luke S.P.
Highlights: W. confusa can be mis-identified by some phenotypic methods, but MALDI-ToF provides good discrimination. W. confusa endocarditis can cause destructive valvular disease. W. confusa is resistant to glycopeptides, but susceptible to penicillin and gentamicin. Abstract: Background: Weissella confusa, a Gram positive coccobacillus, is a rare cause of human disease. They are vancomycin resistant, bile aesculin positive, lactic acid fermenters previously classified as members of the Leuconostoc and Lactobacillus genera. Among the 19 recognised species of Weissella, W. confusa is most frequently associated with human infection, however as its name suggests establishing its pathogenicity and correctly identifying it using traditional phenotypic testing platforms can be challenging. Case report: We present a case of W. confusa endocarditis in a male from Ghana where W. confusa is used in the fermenting process of commonly consumed food products. We discuss the microbiological diagnostic processes, including identification of this organism through use of matrix-assisted laser-desorption ionisation/time-of-flight (MALDI-ToF), and how the laboratory derived susceptibility tests were interpreted and applied to construct a successful therapeutic regime for infective endocarditis. Conclusions: We review the literature around cases of invasive W. confusa disease, contextualising this organism in terms of relevance to patients who are immunocompromised or who have indwelling vascular access devices.